2017
DOI: 10.1097/md.0000000000008528
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of acute acquired comitant esotropia in the Chinese populations

Abstract: Acute acquired comitant esotropia (AACE) is an unusual presentation of esotropia that occurs after infancy. This study was aimed to study the clinical features and the differences between children and adult patients with AACE in the Chinese populations.This was a retrospective analysis of patients diagnosed with AACE over 4 years; 69 patients (25 females and 44 males) were identified. The patients were divided into 3 groups: < 10 year-old (n = 6, 8.7%), 10–18 year-old (n = 23, 33.3%), and ≥18 year-old (n = 40,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
26
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 21 publications
12
26
4
1
Order By: Relevance
“…Adults had higher myopia compared with younger children aged <10 years. These findings are in line with a previous study 15 that demonstrated children under 10 years had mild hyperopia and children aged 10–18 years had mild myopia, whereas adults had moderate to high myopia. Twelve patients with refractive error were prescribed spectacles.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Adults had higher myopia compared with younger children aged <10 years. These findings are in line with a previous study 15 that demonstrated children under 10 years had mild hyperopia and children aged 10–18 years had mild myopia, whereas adults had moderate to high myopia. Twelve patients with refractive error were prescribed spectacles.…”
Section: Discussionsupporting
confidence: 93%
“…The older age of onset observed in our study may explain why the Bielschowsky type was the most common etiology of AACE; this type is caused by prolonged uncorrected myopia and excessive near work in adults, which results in an imbalance of the convergence and divergence tone of the extraocular muscle and an increased force of the medial rectus muscles, leading to esotropia. 15–17 Moreover, our findings support the hypothesis that in Asian populations, AACE is more common in older children and adults than in younger children 15 for the same aforementioned reason.…”
Section: Discussionsupporting
confidence: 82%
“…Fu et al found that the mean deviation of esotropia in younger children was significantly larger than that in older children and adults in the Chinese population. A younger onset age may be a characteristic of AACE and may also be associated with esotropia deviation [11]. In our study, the younger patients experienced worse preinjection stereopsis and larger preinjection deviations for near and distance.…”
Section: Discussionsupporting
confidence: 46%
“…Some AACE cases were neuroimaging study-negative, systemic disease-negative, and without a history of neuro-or anesthesia-related medication use. Such AACE cases were associated only with refractive errors and binocular dysfunction, such as decompensated esophoria and high myopia, which were generally considered benign or functional [3,4,11,12]. AACE causes uncomfortable diplopia and substantially affects the quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the angle of deviation was larger in younger than in older children and adults. These findings are consistent with the results published by Fu et al, who described a large series of 69 Chinese patients with AACE, and with the series reported by Spierer, in which 9 of 10 adults with AACE were myopic [25,26].…”
Section: Discussionsupporting
confidence: 93%